2022
DOI: 10.1021/acs.iecr.2c01479
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Earth Metal-Induced Hydrogenation of the CaO-Captured CO2 to Methane at Room Temperature

Abstract: CaO is promising to be widely used to capture CO2. The produced CaCO3 can be considered as solid CO2, which is also a plentiful, convenient, and useful carbon resource. Here, for the first time, we report that an alkaline earth metal can selectively induce the hydrogenation of the CaO-captured CO2 (namely, the produced CaCO3) to CH4 under room-temperature ball-milling conditions. The effects of ball-milling conditions and different catalysts on the methanation performance were studied. The results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recently, there has been interest in the catalytic hydrogenation of carbonates to hydrocarbons. According to the research by Rao et al, carbonate can be transformed into CH 4 at 823 K in the presence of the catalyst Co/CoO/CaO . They also reported that CaCO 3 could be hydrogenated to create C 1 –C 3 hydrocarbons in the temperature range of 573–873 K under atmospheric pressure using the catalysis of iron catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been interest in the catalytic hydrogenation of carbonates to hydrocarbons. According to the research by Rao et al, carbonate can be transformed into CH 4 at 823 K in the presence of the catalyst Co/CoO/CaO . They also reported that CaCO 3 could be hydrogenated to create C 1 –C 3 hydrocarbons in the temperature range of 573–873 K under atmospheric pressure using the catalysis of iron catalyst .…”
Section: Introductionmentioning
confidence: 99%